International Train the Trainer antibiotic stewardship program for pharmacists: Implementation, sustainability, and outcomes. Issue 5 (6th April 2020) - Goff, Debra A.; Bauer, Karri A.; Brink, Adrian; Kolman, Sonya; Mendelson, Marc; Messina, Angeliki P.; Schellack, Natalie; van den Bergh, Dena
Abstract: Introduction: The high burden of infectious diseases in South Africa and the misuse and overuse of antibiotics are driving antibiotic resistance to the extent that bacterial infections are commonly difficult to treat, and in some cases, are untreatable. Implementing antibiotic stewardship (AS) is challenging due to a lack of physicians and pharmacists trained for treating infectious diseases. Objectives: To describe the implementation, outcomes, and sustainability of a collaborative Train the Trainer (TTT) AS pharmacist mentoring program between a US hospital and hospitals in South Africa. Methods: The partnership formed in 2012 around the five pillars of global engagement: shared leadership, mutually beneficial partnership, local needs‐based care, host‐driven education, and sustainability. The TTT program included bilateral site visits, development of pharmacists' AS skills, research, and paying‐it‐forward. Results: Ten pharmacist mentees from private (n = 6) and public hospitals (n = 4) completed the TTT program between 2013 and 2019. Subsequently, mentees were able to transfer their AS skills to train an additional 120 pharmacists with no prior AS experience. These pharmacists made over 40 000 AS interventions in 60 hospitals across seven provinces. Mentees coauthored 12 AS publications, 1 book chapter, 4 invited commentaries in South African, US, and international journals, and presented 28 AS abstracts at national and international conferences. For nine of the mentees, this was their first AS research experience and publication. One mentee introduced an AS module to the pharmacotherapy course and 160 students completed the module. The first clinical pharmacy AS rotation was established. Mentees participated in national AS committees and engaged in AS public awareness work by delivering radio and TV interviews. Conclusions: Shared leadership between the US and South African mentors led to developing a TTT program that met their local needs. The TTT program achieved its goal of helping to develop South African pharmacists capable of implementing sustainable AS interventions that improve patient care.